PENDAMPINGAN PENGOLAHAN JAJAN BEGINA DAN PENERAPAN HYGIENE SANITASI KELOMPOK SRI YADNYA DI DESA BEDULU, BLAHBATUH, GIANYAR - I Gusti Ayu Ika Monika Prastyandhari; Ni Putu Widiastuti; Gerson Feoh; Ni Kadek Dwipayani Lestari; Ni Kadek Ericka Junita Dewi Mantara Putri; Liefie Julieser Ishiwata (Universitas Mataram, 2026)
Gigia snacks are one of the traditional Balinese snacks that are similar in shape to rengginang with a savory and sweet taste. The problems faced by partners are limited production support equipment, lack of knowledge of partners related to hygiene and sanitation processing, lack of training on snacks to improve the quality of snacks, lack of packaging, lack of financial management and production SOPs, lack of social media and brochures. The method used in this activity is mentoring and training with the Sri Yadnya group of Blahbatuh Village, Gianyar. Mentoring and training are carried out by the service implementation team. After the service activity, an activity evaluation process will be carried out with pre and post test methods. The results of the service show an increase in work efficiency from the equipment provided to partners. The production time which is usually 3 hours can be completed within 2 hours. In the previous packaging assistance, plastic packaging was used and after being provided with assistance and training using the product, it was packaged using a portable electric press, then sealed using duplex cardboard packaging, so that the shelf life of the snacks was longer from 2 weeks to 1 month, the product remained crispy at room temperature. In addition, there is an increase in partner knowledge by 30% in the field of hygiene and sanitation training and financial management . The conclusion of this activity is; Partners' insights and knowledge have increased, related to the use of equipment, the application of hygiene and sanitation, the processing of snacks according to recipes, the use of packaging equipment; partners have skills in processing Begina snacks according to sanitary standards and hygiene; Begina snack products have the brand